Mediação nos contratos coligados - Oliveira, Luciana de Souza e (2019)
The related contracts present as an organization of a business complex, in such a way as to reveal, in many cases, the continued relationship between several components, a scenario conducive to the occurrence of various conflicts. It is hoped that the law will be able to progress more and better in understanding the aspects that make up the penalties and relationships reported in related hires, thus contributing to the resolution of conflicts and, if possible, to the reciprocal parties. used. The doctrine has endeavored to define the characterization and the related hiring system and the proper handling of its legal issues, which in no case, in the event of controversy, should be aligned with the multiport system, using automatic component solutions. (an example of mediation, conciliation and negotiation) or heterocompositive (an example of arbitration and court proceedings). Given or exposed, this dissertation, supported by a broad bibliographical research, discusses different concepts by Brazilian and foreign authors about affiliate contracts and, at the same time, highlights a mediation as a very appropriate resource for conflict analysis there, issues that also was developed validating and conceptualizing through bibliographic research. Thus, the guiding objectives of the research focusing on the concepts of related contracts and those of mediation, these results will prove to be proposed on the hypothesis of mediation that may indeed be a very effective resource for dealing with conflicts in the commercial sectors, if developed. by competent professional and updated with recent studies on the subject